Impacts of land use change brought by coastal land reclamation projects (1990-2020) in Manila, Pasay, Parañaque on economic development, community, and government - Discar, Giany Marxiamille C. (School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Over the past thirty years, coastal land reclamation projects (CLRPs) have shaped the urban landscape of Metro Manila, particularly in the cities of Manila, Pasay, and Parañaque. Despite their growing prevalence, local research on CLRPs remains limited, especially regarding their implications for real estate planning and development. This study addresses that gap through a thematic analysis of CLRPs built from 1990 to 2020. It evaluates their impacts on three interrelated dimensions: local economic development, community well-being, and governance.